(untitled) (MAUSAM, 1975)
The differences in the thermodynamic structure of the atmosphere over India and the adjoining areas between active and weak monsoon (southwest) periods in the various meteorological sub-divisions are presented. The mean dry bulb and dew point remperatures and equivalent potentioal temperatures during active and weak monsoon were calculated at all the radiosonde stations in India and neighbourhood and studied. The results show that whatever be the monsoon activity, there is no significant change in the dry bulb temperature at any level and the moisture content in the lower tropospheric levels remains high without any appreciable variation. The main change is in the moisture content in the mid-tropospherica levels. The implication of these results in the vertical circulation associated with active and weak monsoon and in the radiation budget are brought out, since the vigorous ascending air in the areas of strong monsoon ultimately subsides slowly over the regions of weak monsoon. The region of the seasonal monsoon trough has been indentified as the area of maximum total energy both in active and weak monsoon is least. This is also the area where convective instability is present upto greater heights than elsewhere. The estimated heights of cb tops are highest in the region of the seasonal monsoon trough. It is also shown that there is no reversal of virtual temperature gradient over the northwest India in the midtropospheric levels during the SW monsoon season.